Tea Polyphenols Attenuate Methamphetamine-Induced Neuronal Damage in PC12 Cells by Alleviating Oxidative Stress and Promoting DNA Repair - Ru, Qin; Xiong, Qi; Tian, Xiang; Chen, Lin; Zhou, Mei; Li, Yi; Li, Chaoying (Frontiers in Physiology, 2019)
DNA integrity plays a crucial role in cell survival. Methamphetamine (METH) is an illegal psychoactive substance that is abused worldwide, and repeated exposure to METH could form mass free radicals and induce neuronal apoptosis. It has been reported that free radicals generated by METH treatment can oxidize DNA to produce strand breaks, but whether it is involved in the neurotoxicity caused by METH remains unclear. Tea polyphenols exert bioactivities through antioxidant related mechanisms. However, the potential neuroprotective effect of tea polyphenols on METH-induced nerve cells damage and the underlying mechanism remain to be clarified. In this study, oxidative stress, DNA damage and cell apoptosis were increased after METH exposure and the expressions of DNA repair associated proteins including the phosphorylation of ataxia telangiectasia mutant (p-ATM) and checkpoint kinase 2 (p-Chk2) were significantly declined after high dose or long time METH treatment in PC12 cells. Additionally, tea polyphenols could protect PC12 cells against METH-caused cell viability loss, reactive oxide species and nitric oxide production, mitochondrial dysfunction, and suppress METH induced apoptosis. Furthermore, tea polyphenols could increase antioxidant capacities and expressions of p-ATM and p-Chk2, and then attenuate DNA damage via activating DNA repair signaling pathway. These findings indicate that METH is likely to induce neurotoxicity by inducing DNA damage, which can be rescued by tea polyphenols. Supplementation with tea polyphenols could be an effective nutritional prevention strategy for METH-induced neurotoxicity and neurodegenerative disease.